Adaptation of human gut microbiota to bariatric surgeries in morbidly obese patients: A systematic review. (March 2018) - Ejtahed, Hanieh-Sadat; Angoorani, Pooneh; Hasani-Ranjbar, Shirin; Siadat, Seyed-Davar; Ghasemi, Nasrin; Larijani, Bagher; Soroush, Ahmad-Reza
Abstract: Background: Bariatric surgeries have turned to be a popular therapeutic option for morbid obesity nowadays. Gut microbiota is supposed to be responsible as a part of the bariatric surgeries success. In this systematic review, we detailed the human studies which investigated the effect of different bariatric surgeries on the composition of gut microbiota. Methods: We did a comprehensive search in PubMed, Web of Science, and Scopus for all clinical trials and longitudinal observational studies documented up to December 2015. Results: Our initial search yielded 1423 articles. After screening abstracts and full texts, 7 articles were included. In 6 studies, the type of surgical intervention was Roux-en-Y gastric bypass (RYGB) where one study assessed vertical banded gastroplasty (VBG), too. Only in one study the effect of laparoscopic sleeve gastrectomy (LSG) had been investigated. RYGB caused an increase in Proteobacteria and a decrease in Firmicutes. LSG led to less severe intestinal microbiota alteration compared to RYGB. Fecalibacterium prausnitzii species with anti-inflammatory properties increased after LSG. However, inconsistent alterations have been shown in abundance of Fecalibacterium species after RYGB. Conclusion: Weight loss after bariatric surgeries are associated with microbiota modifications caused by surgical procedures. Highlights: Gut microbiota is supposed to be responsible as a part of the bariatric surgeries success. RYGB caused an increase in Proteobacteria and a decrease in Firmicutes. LSG led to milder intestinal microbiota alteration compared to RYGB.